Effect of elliptic angle Ï† on the existence and stability of libration points in restricted three-body problem in earth-moon system considering earth as an ellipsoid - Idrisi, M Javed; Amjad, Muhammad (International Journal of Advanced Astronomy, 2015)
This paper deals with the existence and the stability of the earth-moon libration points in the restricted three-body problem. In this paper we have considered the bigger primary as an ellipsoid while the smaller one as a point-mass. This is observed that the collinear and non-collinear libration points exist only in the interval 0Ëš<Ï† < 45Ëš. There exist three collinear libration points and the non-collinear libration points are forming a right triangle with the primaries. Further observed that the libration points either collinear or non-collinear all are unstable in 0Ëš<Ï† < 45Ëš.